SISTER MARY JOSEPH NODULE, A FORGOTTEN NODULE - Akram, Muhammad; Baig, Muhammad Asif; Ali, Saadat (Journal of Ayub Medical College Abbottabad, 2014)
Metastatic cancer of the umbilicus, known as Sister Mary Joseph nodule, is typically associated with visceral malignancy. It is an uncommon and rare presentation. It indicates disseminated disease and poor prognosis. Physicians need to be aware of this rare clinical condition so that they can promptly diagnose the primary cancer. Keywords: Sister Mary Joseph, umbilical nodule, gastric adenocarcinoma